Tears rendering in extreme expression by using SPH method and gravity parameters - Mohd. Rahim, Mohd. Shafry (Springer, 2014)
The simulation of fluid generation and the Smooth Particle Hydrodynamic (SPH) method has been discussed as an explanation for extreme expression, followed by tears simulation which includes creating tears using SPH and tears effect rendering. Furthermore, the testing and the evaluation for creating tears simulation with different effects and cases were applied. Accordingly, this paper explains how to control the crying with the facial animation expressions which are used to simulate the extreme expressions. Additionally, the results of various aspects of this study and the different kinds of crying were simulated and explained. Finally, the measurements of frame rates for different parts of tears simulation by using Fraps software have been explored.